Pemanfaatan Serbuk Limbah Gypsum Sebagai Substitusi Parsial Komposisi Tanah Liat dan Abu Daun Bambu Sebagai Substitusi Parsial Komposisi Sekam Padi Terhadap Batu Bata Merah - Rani Damayanti; Siti Fahitha Muharromah; Bambang Setiabudi; Hartono Hartono (Jurnal Sipil dan Arsitektur, 2024)
The increase in development has increased the need for construction materials. One material often used is red bricks as a wall pair or barrier in the house. On the other hand, red bricks also have added value in terms of aesthetics. Generally, the main ingredients of bricks are clay, rice husks, and water, which are molded in a square shape, and the hardening process is through burning until it turns red and hard. By looking at the high need for bricks, this research aims to make a mixture innovation to the composition of bricks, namely adding gypsum powder waste to the composition of clay and bamboo leaf ash to the composition of rice husks. The variation used in this innovation is 2.5% gypsum powder waste in each sample of mixed red bricks, then in the variation of bamboo leaf ash by 5% and 7.5%. Like conventional red bricks, the size of red bricks is 23cm long, 10cm wide, and 5cm thick. The test results on conventional red bricks have a compressive strength value of 1.27 MPa and water absorption of 11%, while in red brick innovation, the optimal compressive strength value is in the variation of 2.5% gypsum powder waste in clay and 5% bamboo leaf ash in rice husk has a compressive strength value of 1.58 Mpa and water absorption of 9% where mixed red bricks are superior to conventional red bricks.